Effect of Water on Some Mechanical Properties for Gravel Particles/Polyester Composites - Essa, Abbas Fadhil; Jadah, Ahmed; Jerjack, Najlaa (Al-Nahrain Journal of Science, 2018)
In view of the developments of industrial applications, this happened in recent years and the need to use composite materials in general and polymer composite especially in the various industrial applications developed. This research deals with the study of the effect of water on some mechanical properties of polymer composite and its matrix material is unsaturated polyester (UPE) reinforced by gravel particles (different types) with particles size of (121.74 nm) for type (Ι) and (100.16 nm) for type (ΙI) as a fillers with different weight percentages (10, 20, 30, 40) % to prepare polyester composites. The molding method was used to prepare polyester and its composites sheets. The mechanical properties were studied including flexural strength and Young's modulus for the samples at normal conditions (N.C). unsaturated polyester and its composite samples were immersed in water for about 30 days to find the effect of water on their flexural strength and Young's modulus after immersion (A.I).The results showed that the samples of UPE / gravels particles type ΙΙ composite gained highest values of flexural strength (110.9MPa) as compared with other composites at (N.C) and showed that the samples of UPE / gravels particles type Ι composite gained highest values of Young's modulus (6.49 GPa) as compared with other composites at (N.C). Finally, The results showed decrease in values of Young's modulus for all the samples after immersion (A.I) as compared with the samples at (N.C) and showed decrease in values of flexural strength for all the samples except for the composite material of UPE / gravels particles type Ι at weight percent (10, 20) % which showed an increase in the value of flexural strength after immersion (A.I).